Exploring the potential of GO-based composite hydrogels and their swelling property for controlled drug delivery - Ayucitra Aning; Ju Yi-Hsu (E3S Web of Conferences, 2024)
Swelling studies are essential for hydrogels with potential applications in biomedical areas, as the materials will be exposed to biological fluids. This study obtained composite hydrogels by physically cross-linked carboxymethyl cellulose (CMC) with GO. CMC is known to be non-toxic, non-allergenic, and possesses good biodegradability. To produce GO, a ‘greener’ modified Hummers’ method was first employed by removing the use of sodium nitrate in the oxidation process to avoid the generation of toxic NOx gases. Iron (III) chloride was then used as a cross-linker in composite preparation. The responses of GO-CMC hydrogel networks to various solvents and temperatures were studied by measuring their swelling property. The solvents included water, salt solution, ethanol, hexane, and phosphate buffer solutions with various pH (pH 2.1, 5.0, and 7.4). The effect of temperature on swelling was studied at temperatures of 25, 35, and 45oC. Results showed that the presence of GO within CMC matrixes altered the structures and properties whilst enhancing the swelling property compared to its native CMC hydrogel, at studied temperatures. It was also observed that the swelling property of GO-CMC composite hydrogels depended significantly on the pH of the environment, a great attribute for drug carriers with pH-sensitive behavior..